2021
DOI: 10.1021/acsaem.1c02666
|View full text |Cite
|
Sign up to set email alerts
|

Li-Doped Chemical Bath Deposited SnO2 Enables Efficient Perovskite Photovoltaics

Abstract: Electron transport layers (ETLs) based on tin oxide (SnO2) get wide attention in planar perovskite solar cells (PSCs), with the merits of high electron mobility and low-temperature fabrication. However, the poor electron extraction ability of SnO2 seriously deteriorates the performance of devices. Herein, we report an optimized strategy for SnO2 films to enhance the carrier transport. The dense and pinhole free ETL films with Li doping are developed by chemical bath deposition. Li-doped SnO2 shows better energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…After the introduction of NiCl 2 ·6H 2 O, the intensity of hydroxyl (or oxygen vacancies) decreased significantly, indicating that the oxygen vacancies were effectively passivated. 41 The reduction of oxygen vacancy defects will improve V OC . Therefore, the successful introduction of NiCl 2 ·6H 2 O will considerably improve the ETL.…”
Section: Resultsmentioning
confidence: 99%
“…After the introduction of NiCl 2 ·6H 2 O, the intensity of hydroxyl (or oxygen vacancies) decreased significantly, indicating that the oxygen vacancies were effectively passivated. 41 The reduction of oxygen vacancy defects will improve V OC . Therefore, the successful introduction of NiCl 2 ·6H 2 O will considerably improve the ETL.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al used the CBD method to deposit a tin oxide film on the perovskite light-absorbing layer and used lithium chloride (LiCl) as a dopant to improve the morphology of SnO 2 by controlling the reaction time and pH value. 73 The energy level arrangement and electrical properties of Li-doped ETLs were reported. They found that Li doping can improve electron extraction ability and conductivity.…”
Section: The Preparation Methods Of the Sno2 Etlmentioning
confidence: 99%
“…As the alkali metal is incorporated as an interstitial dopant within the perovskite, it can passivate and immobilize the charged defects, thus enhancing the performance and stability of the PSCs 5,14 . The ETL can also benefit from the migrated Li + ions, as carrier extraction is enhanced by improved interfacial band alignment and conductivity of the ETL 15,16 . Despite the reported beneficial effects of interstitial doping, our recent study unraveled possible detrimental effects that are caused by induced microstrain, particularly for widely used formamidinium lead tri‐iodides (FAPbI 3 ) based perovskites 5 .…”
Section: Introductionmentioning
confidence: 97%
“…5,14 The ETL can also benefit from the migrated Li + ions, as carrier extraction is enhanced by improved interfacial band alignment and conductivity of the ETL. 15,16 Despite the reported beneficial effects of interstitial doping, our recent study unraveled possible detrimental effects that are caused by induced microstrain, particularly for widely used formamidinium lead tri-iodides (FAPbI 3 ) based perovskites. 5 Thus, we were motivated to study side effects caused by the Li + ion migration in FAPbI 3 PSCs.…”
Section: Introductionmentioning
confidence: 99%